An assessment of the creativity and sensuality of the residential spaces of selected Filipino visual artists - Mauricio, Inna Victoria Feanne H.
This study examined how creativity and sensuality manifested in the interior design of the residential spaces of three Filipino visual artists. The research utilized a qualitative approach and employed observation, interview, and visual documentation to gather data. The sampling design was purposive. The subjects were selected Filipino artists residing within Metro Manila and working in various types of visual art. Each artist was asked to select the three most significant areas in their residence for the study; they were free to select any type and size of area as long as they could explain why the area was significant to them. Instrumentation included pen and paper and a digital SLR camera. The gathered data was composed of descriptive text narratives and digital photographs. The treatment of data involved assessing the interior design of the spaces against the parameters of creativity and sensuality defined in this study. The findings revealed that all three artists'space showed high levels of creativity, while two out of three artists' spaces exhibited high levels of sensuality. Creativity and sensuality were most prominent in the interior design aspect of furnishings and decor. The characteristic of creativity most prominent in the artists' spaces was "reflective", meaning, the spaces expressed the artists' personalities and experiences. The characteristic of sensuality most shown in the artists' spaces was "visually stimulating". In conclusion, creativity and sensuality manifested in varying levels in the artists' spaces. The interesting and meaningful possessions of the artists influenced the creativity and sensuality of their spaces. The fact that these artists work primarily in visual media was reflected in the type of sensuality apparent in their spaces. Furthermore, the study revealed the difficulty of evaluating creativity and sensuality - highly experiential ideas which may only be captured in writing in a limited manner.